2018
DOI: 10.1016/j.tafmec.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low temperature tensile properties on crack driving force for Arctic applications

Abstract: Many petroleum companies expand their activities further north towards the Arctic region, resulting in design temperatures down to −60• C, which is much lower than what is usual for most current petroleum installations. As properties of steels are temperature dependent, it is of great interest to evaluate the effects of low temperature on the crack driving force in steels. The present work investigates these effects numerically using finite element (FE) models of single-edge-notchedtension (SENT) specimens wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Ren 2 carried out tensile tests of a 420-MPa steel with temperature ranging from 0°C down to −90°C and found that the Lüders strain [3][4][5] increased as the temperature decreased. It has been demonstrated that there are considerable oil and gas resources in the Arctic region 1 ; the low-temperature effect should be considered in the selection of structural steels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ren 2 carried out tensile tests of a 420-MPa steel with temperature ranging from 0°C down to −90°C and found that the Lüders strain [3][4][5] increased as the temperature decreased. It has been demonstrated that there are considerable oil and gas resources in the Arctic region 1 ; the low-temperature effect should be considered in the selection of structural steels.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that decreasing temperature increases the yield strength of most steels. Ren 2 carried out tensile tests of a 420-MPa steel with temperature ranging from 0°C down to −90°C and found that the Lüders strain [3][4][5] increased as the temperature decreased. For most structural steels, as the temperature decreases continuously, the fracture behaviour will transform from ductile to brittle (DBT), [6][7][8][9][10][11][12] reducing the steels' ductility and fracture toughness.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation on the Lüders plateau effect on crack driving force by Dahl have demonstrated that the existence of Lüders plateau intensified the crack driving force. Larger Lüders plateau corresponds to higher crack driving force (Dahl et al, 2018). Ductile crack growth lies in the competition of crack driving force and crack resistance.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that most structural steels show obvious temperature dependent mechanical properties, such as yield stress, ductile-brittle fracture transition behavior. Previous investigations demonstrate that for some steels, the so-called Lüders plateau which is influenced by loading rate, ferrite grain size, yield stress, et al may occur in uniaxial tension test (Beardsmore et al, 2013;Dahl et al, 2018;Hallai and Kyriakides, 2013;Han et al, 2017;Liu et al, 2015;Mazière et al, 2017;Ren et al, 2015;Tsuchida et al, 2006). It has been reported that lowering testing temperature will increase the Lüders plateau length, see Fig.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation